Emerging Therapies in Hematopoietic Stem Cell Transplantation - Reddy, Pavan (Biol Blood Marrow Transplant, 2012)
Despite improvements to hematopoietic stem cell transplantation (HSCT) over the past several decades, further advances are necessary to achieve: improved control of toxicities like graft-versus-host disease (GVHD); enhanced immunologic reconstitution post transplantation; and reduction in relapse risk via enhancement of graft-versus-tumor (GVT) responses. Achieving these disparate HSCT goals will likely require the introduction of novel therapeutic agents to the current armamentarium. In this chapter we outline preclinical and early phase clinical data indicating the potential of proteasome-inhibitor therapy (bortezomib), hypomethylating agent therapy (azacytidine), and histone deacetylase-inhibitor therapy (vorinostat) to help improve HSCT outcomes.